The Living sea - Stoneman, John. ([Canada] Maxima Film Corp., 1995)
The Sunset sea examines the diversity of marine life along the west coast of North America. Signals looks at the wide range of methods used by creatures under the sea to communicate with each other.
Sunset sea (25 min.) -- Signals (25 min.)
Producer, Sarah Stoneman ; director, John Stoneman ; writers, Joseph Blasioli, John Stoneman.
Keywords: Marine biology -- British Columbia -- Pacific Coast; Marine animals -- British Columbia -- Pacific Coast